Penilaian Kualitas Layanan Undangan RSVP Digital dengan menggunakan Importance Performance Analysis (IPA) - Mohammad Ilham Pratama Elba Wahid; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Service is any activity or benefit offered by one party to another and is essentially intangible and does not result in ownership of anything (Kotler, 2005). In the city of Malang, Redd One Digital is a service provider that works with event organizers. This department collaborates using technology by offering RSVP digital invitations and digital guest books. This department is one of the business actors who carry out a pivot strategy by providing information services towards digital technology such as making online invitations that can be used for various events. However, since Redd One Digital has implemented a pivot strategy, until now, Redd One Malang's digital invitation service has not evaluated the quality level of the digital invitations they have made. Based on this description, it is necessary to conduct an assessment of service quality using Service Quality and determine the Importance Performance Analysis (IPA) quadrant grouping. From the results of my research and analysis on the quality of services provided by Redd One Digital Malang, there are a total of 11 attributes that need improvement based on the attributes contained in the first and third quadrants of the Importance Performance Analysis.